Detecting Forgery : Forensic Investigation of Documents - Nickell, Joe (EBL-Schweitzer, 2015)
Cover; Title; Copyright; Contents; Acknowledgments; Introduction; Part One. Handwriting; 1. The Written Word; Evolution of Handwriting; Graphology versus Science; The Forensic Approach; 2. Examining Handwriting and Typewriting; Class versus Individual Characteristics; Examplars and Standards; Identification Factors; Handwriting Comparison; Disguised Writing and Printing; Illegibility and Decipherment; Typewriting and Other Mechanical Forms; 3. Forged Writing; The Forger's Techniques; Warning Signs of Forgery; Detecting Nonforgery Fakes; Part Two. Additional Aspects